Prediction Analysis of Rice Field Conversion in Badung Regency Using Big Data Method - I Wayan Angga Pratama; Ketut Budi Susrusa; I Made Sudarma (Universitas Dwijendra Press, 2026)
Badung Regency is situated in Bali Province and encompasses an area of 418.52 km². With the development of time and the dynamics of development and population growth, the existence of land has begun to be disturbed. One of the problems closely related to the existence of rice plants is the increasing conversion of agricultural land. This study aims to determine the extent of rice field conversion using Big Data. The data used in this study includes rice field area (ha), population (people), per capita GDP (IDR), and the share of agriculture in GDP (%) from 2018 to 2024, sourced from BPS and the Agriculture and Food Security Department of Bali Province. The results of the study indicate that the forecasting method using the Backpropagation algorithm can be used to provide an approach for the years 2025 and 2026. The Backpropagation design uses MAPE of 0.00012, categorized as good forecasting. Therefore, it is recommended to conduct further research focused on each regency, as each regency has distinct characteristics in food data collection methods, particularly for rice. Future research should develop this forecasting method by incorporating machine learning techniques to achieve more accurate forecasting results